Masker Gel Peel-off Kombinasi Ekstrak Daun Pegagan (Centella asiatica) dan Niacinamide: Formulasi, Efektivitas Antibakteri, Aktivitas Antioksidan, dan Iritabilitas - Chasanah, Uswatun; Rahmasari, Dyah; Desinta, Cynthia Ayu; Febriana, Fella; Pertiwi, Hera Nadila; Olivia, Nanda Trisna (BORNEO JOURNAL OF PHARMASCIENTECH, 2026)
Acne is a skin disease caused by pathogenic bacteria such as Propionibacterium acne and Staphylococcus aureus. Pegagan leaves (Centella asiatica) are a natural ingredient that has antibacterial properties. This ingredient was combined with niacinamide as an antioxidant in a peel-off gel mask preparation to make it easier to use. This study aimed to determine the best peel-off gel mask formula for pegagan leaf extract and niacinamide based on the evaluation of characteristics and stability and antibacterial, antioxidant, and irritant effects on the skin. In this study, we used experimental methods. Pegagan leaf extract was varied in concentrations of 1.25%, 2.5%, and 5%. In the characteristic test, which included organoleptic tests, viscosity, spreadability, drying time, and pH value, we obtained the preparation results with good characteristics. The preparation has good physical stability but is not chemically stable, and it was tested using the freeze-thaw method. The results of the antioxidant test of the preparations in the three formulas showed weak antioxidant activity, with IC50 values ​​of F1 228.54ppm, F2 147.22ppm, and F3 120.35ppm. The results of the antibacterial test showed that the preparations had more potential for Propionibacterium acne bacteria, with results of F1 15.43±1.52mm, F2 15.57±0.82mm, and F3 17.37±0.34mm. The three formulas found no irritation effects using the HET-CAM method. Based on the results of this study, the peel-off gel mask of pegagan leaf extract combined with niacinamide has the potential as an anti-acne preparation.